The Impact of Personality on Second Language Acquisition: Insights from A Visually-Impaired Student - Ana Humardhiana (IAIN Syekh Nurjati Cirebon, 2024)
The success of second language acquisition (SLA) is influenced by both external and internal factors, with internal factors comprising individual differences (IDs) among learners. Among these IDs, personality has increasingly been recognized as a significant determinant in SLA success. This study investigates the impact of personality on SLA of a visually-impaired student learning English. Employing a case study method, the research focuses on a fifth-grade student with congenital visual impairment. Data were collected through observation, documentation, and interviews to provide an in-depth analysis of the participant’s personality in relation to SLA outcomes. The findings reveal that three personality traits—openness to experience, neuroticism-emotional stability, and extraversion-introversion—exert direct influences on the learner’s SLA. Additionally, two traits, conscientiousness and agreeableness, have indirect impacts. This study aims to offer a comprehensive understanding of the interplay between personality traits and SLA among visually impaired learners, providing valuable insights for English language teachers to address learners' IDs effectively. Furthermore, it contributes to the limited body of research on SLA and personality traits within the context of visually impaired learners, serving as a reference for future investigations in this area.